1956
DOI: 10.1037/h0043671
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral effects of ionizing radiations.

Abstract: The effects of high-energy radiation on pre- and neonatal development, the adult nervous system, learning and performance, and sensory functions are described. Though the number of available studies are few, there is evidence to suggest that: (1) the adult nervous system is relatively radioresistant; (2) learning functions are relatively unaffected by lethal or sublethal dosages of radiation; (3) hearing acuity and thresholds to dark adaptation increase as a result of radiation; and (4) the fetal nervous syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

1966
1966
1975
1975

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 65 publications
0
19
1
Order By: Relevance
“…The reason for this discrepancy is unknown. If only the Z strain had been used in experiments I and II, the conclusion would have been that no learning decrement had been pro duced by X-radiation as the experiments of many investigators have sug gested (Furchtgott, 1956)* Since these two experiments showed a strain dependency, the results did not refute the work of other investigators, instead, the importance of the genotype of animals regarding their response to X-radiation (as measured by maze learning) was demonstrated.…”
Section: Results Of Experiments IVcontrasting
confidence: 34%
See 2 more Smart Citations
“…The reason for this discrepancy is unknown. If only the Z strain had been used in experiments I and II, the conclusion would have been that no learning decrement had been pro duced by X-radiation as the experiments of many investigators have sug gested (Furchtgott, 1956)* Since these two experiments showed a strain dependency, the results did not refute the work of other investigators, instead, the importance of the genotype of animals regarding their response to X-radiation (as measured by maze learning) was demonstrated.…”
Section: Results Of Experiments IVcontrasting
confidence: 34%
“…The analysis of variance for transformed errors per error trial scores of experiment IV (the symbols were defined in (Table 25) (Table 27) (Furchtgott, 1956)* However, there have been exceptions* Blair and Arnold (1956) reported an Increase in maze retention following cranial X-radiation»…”
Section: Results Of Experiments IVmentioning
confidence: 99%
See 1 more Smart Citation
“…Research prior to 1965 concerning radiation effects on behavior is reviewed in Furchtgott (1956Furchtgott ( , 1963 and in two symposia edited by Snider (1962, 1964). Kimeldorf and Hunt (1965) review, among other things, the effects of radiation on sensory capacities, on performance capacity, on psychological processes, and on behavioral activation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Lindsley (1962) suggests that high levels of irradiation are associated with performance decrement and low levels tend to enhance performance. According to Furchtgott (1956), the effectiveness of irradiation in changing the behavior of mammals increases with ion density. Meier (1964) supports the idea that the types and magnitudes of behavioral changes as a result of irradiation are a function of the age of the animals at exposure.…”
Section: Introductionmentioning
confidence: 99%